KORELASI SUPERVISI AKADEMIK DAN MOTIVASI KERJA KEPALA SEKOLAH DENGAN KINERJA GURU SEKOLAH MENENGAH ATAS - Tarmudi, Muh; Wahyudi, Wahyudi; Syukri, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to describe and assess the correlation of academic supervision and motivation to work with the school's head teacher performance in the National High School District of Sanggau. This study uses a quantitative approach to the correlation technique. Data were obtained from 64 samples of school teachers in the National High School District of Sanggau. Data was collected by questionnaire and analyzed using multiple regression techniques. The results of correlation analysis of single and multiple regression showed that; (1) there is a positive and significant correlation academic supervision by the school head teacher performance, (2) there is a positive and significant correlation motivation to work with the school's head teacher performance. The results of multiple correlation analysis showed that the academic supervision and motivation to work together principals positively and significantly correlated with the performance of teachers in the National High School District of Sanggau. Keywords: Academic Supervision, Work Motivation, Teacher Performance